Enhancing graduate employability by bridging SKAOs gaps through job-based curriculum development - Ismail , Shaira; Shafie, Dalili Izni; Abd. Rahman, Nurul Hayani; Shafie, Nani Ilyana (International Journal of Accounting, Finance and Business, 2025)
This research project aims to develop a job-based curriculum framework that aligns graduates’ skills, knowledge, abilities, and other attributes (SKAOs) with industry requirements, in enhancing graduates' employability. The study will analyze 3,000 job advertisements sourced from platforms such as MyFutureJobs (under the Ministry of Human Resources) and JobStreet Malaysia to identify the specific job tasks, skills, and competencies required by employers. By examining the job descriptions (JD) and job specifications (JS), the research will determine the core SKAOs expected by industries to ensure higher education curricula are up-to-date and relevant to the labor market. To validate the findings, endorsement sessions with selected employers and personnel from the Ministry of Human Resources will be conducted to validate the SKAOs (Job Description and Job Specification with Assigned Level/Ranking, Degree of Importance, and Corresponding Weightage) in addressing the gaps to formulate the relevant Training & Development Programs. This approach seeks to close the gap between academic training and industry demands, ensuring graduates are equipped with the skills necessary for immediate entry into the workforce. The project also targets jobless alumni and final-semester students through tailored training and development programs managed by UiTM Pulau Pinang Branch, in coordination with other relevant programs provided by the Ministry of Human Resources. These programs aim to address the gaps in graduates' SKAOs, ensuring they are prepared to meet industry expectations. In doing so, the higher education institutions (HEIs) will continuously adapt their curricula to reflect evolving labor market needs, providing graduates with the competencies required to thrive in their professions.